Non-Organic Dielectric Layers for Graphene and Flexible Electronics - Antonova I V (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2016)
Future electronics technology is expected to develop from rigid to flexible devices, which requires breakthroughs in materials' properties, especially flexibility, in combination with desirable electrical insulating, semiconducting and metallic properties. Recently emerging 2D materials such as graphene are promising for an active conductive layer in a wide spectrum of flexible electronic devices. Developing optimized dielectrics for the graphene active layer is critical for graphene applications. The advances and limitations of qualitatively different traditional dielectric metal oxide layers (high-k dielectrics Al2O3, HfO2, and ZrO2) used as a gate in graphene field effect transistors on flexible substrates are considered in the first part of the present review. Its second part analyzes properties of novel dielectric materials (h-BN, Y2O3, graphene oxide, fluorinated graphene, composite dielectrics, ion gels) used for graphene transistors. Dielectric layers fabricated from fluorinated graphene or in combination with graphene oxide are the most promising graphene based flexible and transparent electronics.